Using Directional Deep Brain Stimulation to Co-activate the Subthalamic Nucleus and Zona Incerta for Overlapping Essential Tremor/Parkinson's Disease Symptoms - Falconer, Ramsey A. (Front Neurol, 2018)
This index case report describes a novel programming approach that utilizes the 8-contact directional Deep Brain Stimulation (DBS) lead to effectively control the akinesia, rigidity and tremor of Parkinson's Disease (PD), as well as a severe kinetic tremor of Essential Tremor (ET), in a patient with overlapping symptoms of both PD and ET. Through utilizing a bipolar directional montage on a single segmented contact, symptom control was attained via likely co-activation of the Subthalamic Nucleus (STN) and the adjacent Zona Incerta (ZI). The patient is a 67-year-old professional guitarist with a long-standing diagnosis of ET manifesting with bilateral kinetic tremor, who then developed right lateralizing symptoms indicative of PD. After optimal medical management did not confer sufficient control, he underwent left-sided unilateral DBS targeting the STN. Both intraoperatively and post-operatively, omnidirectional, and directional electrode review resulted in significant akinesia, rigidity, and as well as resting tremor control but failed to sufficiently improve the kinetic tremor. As electrode 2B was shown to be the most efficacious with the largest therapeutic window, a bipolar directional montage on a single segmented contact was tried with the idea of possibly further extending the axial asymmetry of the directional stimulation toward the adjacent ZI to impact the kinetic tremor. This montage resulted in full kinetic and resting tremor control as well as akinesia and rigidity response [2B cathode (–), 2A anode (+), 2C anode (+) (1.4 mA, rate 160 Hz, pulse width 60 μs)]. At 6 months post initial programming, no montage changes have been made, and the patient has experienced a reduction in Motor UPDRS scores from 23 to 3 (evaluated off medication), full resolution of kinetic tremor and normalization of handwriting, as well as significant reduction in his medication requirements. This patient's response to a single segment bipolar directional montage, and lack of response from monopolar directional stimulation in the same area, does suggest the possibility of further axial asymmetric tissue activation and thus co-activation of both the dorsal STN and adjacent ZI. Further modeling and study are warranted.